Hybrid and internationalised criminal tribunals : selected jurisdictional issues - Williams, Sarah, 1974 January 4- (Studies in international and comparative criminal law, 2012)
This book offers a comprehensive and in-depth analysis of Hybrid and Internationalised Criminal Tribunals.